Real-world evidence on efmoroctocog alfa in patients with haemophilia A: A systematic literature review of treatment experience in Europe - Blatný, Jan; Nielsen, Emma Munk; Reitzel, Signe Baattrup; McMillan, Annabell Cajus; Danø, Anne; Bystrická, Linda; Kragh, Nana; Klamroth, Robert (Haemophilia, 2023)
INTRODUCTION: The real-world effectiveness of the efmoroctocog alfa (recombinant FVIII Fc fusion protein, a rFVIIIFc) has been investigated in numerous studies, however, currently, there exists no comprehensive collection of the existing real-world evidence (RWE) on the performance of prophylactic use of rFVIIIFc. AIM: The aims of this systematic literature study were to identify, review, evaluate and collate the RWE of prophylactic rFVIIIFc for patients with haemophilia A reported in Europe. METHODS: We searched Medline and Embase from 2014 to February 2022 to identify publications reporting the effectiveness of rFVIIIFc in patients with haemophilia A. The outcomes of interest were annualised bleeding rates (ABR, AjBR, AsBR), injection frequency, factor consumption, adherence, development of inhibitors and quality-of-life measures. RESULTS: 46 eligible publications (eight full-text articles) were included. rFVIIIFc showed a low ABR in patients with haemophilia A. Studies assessing treatment switching from a standard half-life (SHL) treatment to rFVIIIFc found that the ABR and consumption were reduced in most patients. Studies assessing rFVIIIFc effectiveness reported a median ABR between 0.0 and 2.0 with median injections per week ranging between 1.8 and 2.4 and median doses between 60 and 105 IU/kg/week. Of the studies assessing inhibitor development, only one study reported an incidence of a low titre inhibitor, and no patients developed clinically significant inhibitors. CONCLUSION: rFVIIIFc prophylaxis treatment results in a low ABR across studies in patients with haemophilia A in a European real-world setting, which correlates with findings from clinical trials assessing the efficacy of rFVIIIFc in patients with haemophilia A.
Keywords: imunoglobuliny - Fc fragmenty; Evropa; Half-Life; faktor VIII; Recombinant Fusion Proteins; Europe; rekombinantní fúzní proteiny; hemofilie A; Hemophilia A; Immunoglobulin Fc Fragments; Humans; lidé; Factor VIII; poločas